2022
DOI: 10.3390/genes13122181
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Role and Diagnostic Potential of R-Loops in Cancer and Beyond

Abstract: R-loops are DNA–RNA hybrids that play multifunctional roles in gene regulation, including replication, transcription, transcription–replication collision, epigenetics, and preserving the integrity of the genome. The aberrant formation and accumulation of unscheduled R-loops can disrupt gene expression and damage DNA, thereby causing genome instability. Recent links between unscheduled R-loop accumulation and the abundance of proteins that modulate R-loop biogenesis have been associated with numerous human dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 149 publications
0
13
0
Order By: Relevance
“…In addition to specific degradation of the RNA strand, the helicase Senataxin (SETX) unwinds R-loops and enables subsequent cleavage [ 19 ]. Other helicases, such as RNA helicase aquarius (AQR) and the DEAD Box helicase also resolve R-loops [ 1 , 5 , 9 , 17 , 20 , 21 ]. Similarly, topoisomerase I resolves supercoils, which prevents the formation of transcription-induced R-loops.…”
Section: R-loops—physiological Appearance and Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to specific degradation of the RNA strand, the helicase Senataxin (SETX) unwinds R-loops and enables subsequent cleavage [ 19 ]. Other helicases, such as RNA helicase aquarius (AQR) and the DEAD Box helicase also resolve R-loops [ 1 , 5 , 9 , 17 , 20 , 21 ]. Similarly, topoisomerase I resolves supercoils, which prevents the formation of transcription-induced R-loops.…”
Section: R-loops—physiological Appearance and Regulationmentioning
confidence: 99%
“…In addition to their contribution to neuropathology, R-loops play a critical role in cancer through their complex interplay with known tumor suppressors and oncogenes, as well as due to their central role in maintaining genome stability. Building on previous excellent reviews of the topic [ 1 , 21 , 28 ], we discuss the control of R-loop formation, persistence, and the response to R-loops as a double-edged sword for cancer cells: During tumorigenesis, a dysregulation of proteins that recognize and resolve R-loop and the resulting DNA damage accelerates the mutational burden, enabling cancer progression and promoting resistance. However, an excess of R-loops destabilizes the genome, causing senescence in cancer cells and failures in cell division.…”
Section: R-loops—physiological Appearance and Regulationmentioning
confidence: 99%
“…Interestingly, many diseases are associated with excessive R-loop accumulation or unscheduled R-loop formation. These include neurological or autoimmune diseases as well as cancer [ 12 , 15 , 46 , 47 ]. The latter is not surprising given that persistent R-loops are a source of endogenous DNA damage, which can lead to replication stress and genome instability.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many comprehensive and excellent reviews focused on different aspects of R-loops, ranging from mechanism to function [ 10 , 11 , 12 , 13 , 14 , 15 , 39 , 42 , 46 , 47 ]. Here, we present an updated review of R-loops at a specific locus, telomeres.…”
Section: Introductionmentioning
confidence: 99%
“…Although R-loops are essential mediators of transcription, replication, and DNA repair, unregulated R-loop formation is a major source of genomic instability and potential tumorigenesis [ 19 , 20 , 21 ]. Recent genetic and biochemical studies have identified numerous proteins involved in R-loop regulation, including helicases (e.g., Senataxin), topoisomerases, DNA repair proteins (e.g., BRCA1/2), and RNA splice factors [ 11 ].…”
Section: Introductionmentioning
confidence: 99%